2017
DOI: 10.1007/s00360-017-1064-y
|View full text |Cite
|
Sign up to set email alerts
|

The effect of starvation and re-feeding on vasotocinergic and isotocinergic pathways in immature gilthead sea bream (Sparus aurata)

Abstract: This study describes the responses of the vasotocinergic and isotocinergic systems to food deprivation and re-feeding processes in immature gilthead sea bream (Sparus aurata). The animals were subjected to the following experimental treatments: (1) normal feeding (control), (2) food deprivation for 21 days; and (3) re-feeding for 7 days, beginning 14 days after starvation. The animals were sampled at 0, 7, 14 and 21 days from the beginning of the trial. The pituitary and plasma arginine vasotocin (AVT) and iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 79 publications
5
16
0
Order By: Relevance
“…Endocrine regulation of stress pathways involves several players (Wendelaar Bonga, 2011;Gorissen and Flik, 2016). In fact, our Research Group has assessed the role of different endocrine systems in the gilthead sea bream after different challenges (Arends et al, 1999(Arends et al, , 2000Martos-Sitcha et al, 2013, 2014aSkrzynska et al, 2017;Ruiz-Jarabo et al, 2017,…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Endocrine regulation of stress pathways involves several players (Wendelaar Bonga, 2011;Gorissen and Flik, 2016). In fact, our Research Group has assessed the role of different endocrine systems in the gilthead sea bream after different challenges (Arends et al, 1999(Arends et al, , 2000Martos-Sitcha et al, 2013, 2014aSkrzynska et al, 2017;Ruiz-Jarabo et al, 2017,…”
Section: Discussionmentioning
confidence: 99%
“…A C C E P T E D M A N U S C R I P T among others). Concerning vasotocinergic and isotocinergic pathways, previous results suggested a role of Avt and It hormones in the stress response (Mancera et al, 2008;Cádiz et al, 2015;Skrzynska et al, 2017) together with a stimulatory metabolic role (Sangiao-Alvarellos et al, 2006). However, the complex action of the Avt/It endocrine cascade after FD and HSD conditions in S. aurata in particular, and in teleost fish in general, remains unclear due to the scarce information available.…”
Section: Accepted Manuscriptmentioning
confidence: 97%
See 2 more Smart Citations
“…Furthermore, some studies demonstrated the lack of a direct relationship between primary and secondary responses (Iversen et al., ; Park et al., ), and under long‐term stressful conditions, other hormones could exert both stress and metabolic regulation. Arginine vasotocin (Avt), a neurohypophysial hormone in non‐mammalian vertebrates that presents a pleiotropic function in both stress and metabolic pathways of teleosts, may be another important player mediating metabolic and stress adaptation (Martos‐Sitcha, Wunderink, Gozdowska, Mancera, & Martínez‐Rodríguez, ; Sangiao‐Alvarellos et al., ; Skrzynska, Martos‐Sitcha, Martínez‐Rodríguez, & Mancera, ; Skrzynska et al., ), as the hypothalamic neurons responsible for the synthesis and release of Avt also innervate the adenohypophyseal cells from the HPI axis (Moons, Cambre, Batten, & Vandesande, ). In addition to increasing lactate levels in the control group, HD also reduced hepatic glycogen storage in all diets tested, indicating the activation of glycogenolytic processes to increase the supply of glucose due to energy expenditure resulting from HD condition.…”
Section: Discussionmentioning
confidence: 99%